Modern state and civil society. (Journal of actual problems of jurisprudence, 2016)
In the article the author points out the factors influencing the contents of the discussions on the current state. Among them there are: the processes of globalization; supranational integration; development of communication and transportation technologies, of information society; space exploration; merging of the state elite with the elite groups in economy, business, politics; decentralization; activation of transnational participants (actors) in the international arena, as well as new approaches to understanding of the state.Grater part of the article is devoted to the theory of functions of the state. The author considers the «general function of the state», the main functions of the state and the minimum functions of the state.The author concludes that functioning of state is impossible without society. The theoretical issues of thesocial state, social activities of the state, social statehood are considered in detail.
Keywords: state; society; law; integration; globalization